A systems information model for managing electrical, control, and instrumentation assets - Love, Peter; Zhou, J.; Matthews, Jane; Sing, C.; Carey, B. (Emerald Group Publishing Ltd., 2015)
©Emerald Group Publishing Limited 2044-124X Purpose – The purpose of this paper is to present a systems information model (SIM) that is akin to a building information model (BIM) and can be used by asset managers and staff to make more informed and quicker decisions about maintenance. Design/methodology/approach – The problems associated with managing assets are examined alongside recent international efforts to standardize methods of data collection for meeting the objectives of owners. A case study in the domain of electrical, control and instrumentation (ECI) documentation is examined in detail, with particular reference to the amelioration of errors and omissions in “as built” drawings in order to provide the underlying foundation to support effective asset management (AM). Findings – The findings show that object oriented data models such as SIM provide a robust structure for effective and efficient AM and associated leverage of benefits throughout the entire facility lifecycle of a project. In particular object oriented data enables appropriate and reliable information to be created as a project progresses through its lifecycle, at little cost to the creators. Originality/value – The above special approach to enabling data collection at the point of creation is in alignment with recent Government initiatives such as Construction Operations Building Information Exchange, which are beginning to gather traction within the industry. While the potential benefits for AM of such systems are espoused throughout the industry, there are few successful examples in existence with measurable realization of benefits.